Reflectionless propagation of electromagnetic waves in inhomogeneous magnetoactive plasma with small scale structures - Merkulov, E.S.; Erokhin, N.S. (Вопросы атомной науки и техники, 2013)
It is considered the exactly solvable model of reflectionless electromagnetic wave propagation through the inhomogeneous magnetoactive plasma containing small scale structures of its density. The spatial profiles of wave vector, wave field amplitude, plasma dielectric permettivity have a local relationship. It is investigated their dependence on problem incoming parameters. It has been shown that under some choice of these parameters the spatial profiles of wave vector, wave field amplitude, plasma dielectric permettivity correspond to the magnetoactive plasma case. It has been shown that the plasma inhomogeneity spatial profiles are sensitive enough to incoming parameters variations. Розглянута точно розв’язувана модель безвідбиткового поширення електромагнітної хвилі в неоднорідній магнітоактивній плазмі з мілкомасштабними структурами густини. В моделі просторові профілі хвильового вектора, амплітуди хвилі та діелектричної проникності плазми мають локальні зв’язки. Досліджена їх залежність від вихідних параметрів задачі. Показано, що при деякому виборі цих параметрів просторові профілі хвильового вектора, амплітуди хвилі та діелектричної проникності відповідають магнітоактивній плазмі. Виявлена суттєва чутливість указаних профілів до варіацій параметрів задачі. Рассмотрена точно решаемая модель безотражательного распространения электромагнитной волны в неоднородной магнитоактивной плазме с мелкомасштабными структурами плотности. В модели пространственные профили волнового вектора, амплитуды волны и диэлектрической проницаемости плазмы имеют локальные связи. Исследована их зависимость от исходных параметров задачи. Показано, что при некотором выборе этих параметров пространственные профили волнового вектора, амплитуды волны и диэлектрической проницаемости соответствуют магнитоактивной плазме. Обнаружена существенная чувствительность указанных профилей к вариациям параметров задачи.